(untitled) (Global Journal of Human-Social Science, 2018)
Discrimination and intolerance toward religious communities exists throughout the world, making many people of diverse religions and beliefs vulnerable to extremist thinking and violence. Recognizing the need to actively combat these ideas and promote religious tolerance and pluralism, Hardwired Global piloted a rights based education program to address the underlying fears, misconceptions and biases held by youth that influence their behavior and perceptions of others, making them susceptible to extremist thinking and violence. This resulted in a Teacher-Training Program to equip teachers in three distinct countries in the Middle East and North Africa (MENA) -Iraq, Lebanon, and Morocco -with a rights-based pedagogy and educational resources to integrate greater respect for human dignity, equality, and the rights of people of different religions and beliefs in the culture of the classroom. Analysis of the program has shown statistically significant conceptual change in knowledge, attitudes and beliefs as well as an increase in empathy towards others who believe differently.